Representasi Ruang dan Kebebasan yang Terefleksi dalam Novel Rumah Tanpa Jendela Karya Asma Nadia - Melenia, Vira (Jurnal Bahastra, 2025)
This study investigates the representation of space and freedom in Rumah Tanpa Jendela (House Without Windows), a novel by Asma Nadia, through a literary lens that highlights the psychological and social dimensions of the protagonist’s experience. The research is driven by the central question: how are spatial boundaries and the concept of freedom constructed and reflected in the narrative? Employing a qualitative descriptive method and a structural approach, the analysis focuses on narrative elements—setting, character development, and symbolic motifs—to uncover how space becomes both a literal and metaphorical site of confinement and transformation. The findings reveal that the house without windows serves not merely as a physical location but as a profound metaphor for the social, emotional, and cultural limitations imposed on the main character, Rara. The narrative traces her evolution from a state of passive existence to an active quest for freedom, both intellectually and emotionally. This research concludes that Asma Nadia effectively uses spatial imagery to critique restrictive social norms and to portray a nuanced journey toward self-liberation. The novel thus functions as a literary medium through which themes of gender, oppression, and resilience are powerfully communicated.